2023
DOI: 10.1002/jbt.23330
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine and insulin resistance: Focusing on mechanistic intricacies involve in diabetes associated cardiomyopathy via SIRT1/AMPK and TGF‐β signaling pathway

Abstract: Cardiomyopathy (CDM) and related morbidity and mortality are increasing at an alarming rate, in large part because of the increase in the number of diabetes mellitus cases. The clinical consequence associated with CDM is heart failure (HF) and is considerably worse for patients with diabetes mellitus, as compared to nondiabetics. Diabetic cardiomyopathy (DCM) is characterized by structural and functional malfunctioning of the heart, which includes diastolic dysfunction followed by systolic dysfunction, myocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 146 publications
0
2
0
Order By: Relevance
“…Several studies have reported that OM treatment could improve ischemia/reperfusion and liver failure through the Nrf2/ho-1 pathway [30,31,41]. It has also been shown to have effects on neuroprotection, hepatoprotection, and inflammatory responses through the SIRT1 pathway [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that OM treatment could improve ischemia/reperfusion and liver failure through the Nrf2/ho-1 pathway [30,31,41]. It has also been shown to have effects on neuroprotection, hepatoprotection, and inflammatory responses through the SIRT1 pathway [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Smad3 is pathogenic in cardiovascular diseases, and its overexpression could lead to myocardial inflammation, myocardial fibrosis, and insulin synthesis and secretion disorders, which is a key mediator in the pathogenesis of DCM. Smad7 has a myocardial protective effect, and its overexpression could reverse Smad3-mediated myocardial fibrosis and nuclear factor kappa B (NF-κB)-driven inflammation ( Frangogiannis, 2022 ; Ghafouri-Fard et al, 2023 ; Qin et al, 2023 ; Seksaria et al, 2023 ; Yang et al, 2023 ).…”
Section: Signaling Pathways In Tcm Intervening the Pathological Progr...mentioning
confidence: 99%
“…Alkaloids are plant secondary metabolites composed of polycyclic aromatic frameworks containing one or more nitrogen atoms. Alkaloids have significant hypoglycemic effects, as they can stimulate glucose uptake and regulate insulin secretion, and are considered allosteric activators of AMPK ( Seksaria et al, 2023 ). It is reported that alkaloids can affect the permeability of mitochondrial membrane, regulate the level of calcium ions in mitochondria, and regulate the imbalance of mitochondrial dynamics, thus reducing the occurrence of mitochondrial dysfunction, which is beneficial to the treatment of DCM ( Patalas et al, 2021 ).…”
Section: Plant Secondary Metabolites-based Diabetes Cardiomyopathy Ta...mentioning
confidence: 99%